2010
DOI: 10.1175/2009wcas1014.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Weather on Traffic Intensity

Abstract: This paper focuses on the effect of weather conditions on daily traffic intensities (the number of cars passing a specific segment of a road). The main objective is a general examination of whether or not weather conditions uniformly alter daily traffic intensities in Belgium, or in other words whether or not the road usage on a particular location determines the size of the effects of various weather conditions. This general examination is a contribution which allows policy makers to assess the appropriatenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(107 citation statements)
references
References 21 publications
3
94
0
8
Order By: Relevance
“…This 14% reduction refers to all road weather information together, not only warnings. As mentioned earlier, Cools et al [26] showed that adverse weather tends to reduce traffic volume (roughly by −3% to −7% in the case of Belgium). As the model presented here is based on realized accidents, the estimated (and observed) increase in accident rates includes the just mentioned response effects.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…This 14% reduction refers to all road weather information together, not only warnings. As mentioned earlier, Cools et al [26] showed that adverse weather tends to reduce traffic volume (roughly by −3% to −7% in the case of Belgium). As the model presented here is based on realized accidents, the estimated (and observed) increase in accident rates includes the just mentioned response effects.…”
Section: Resultsmentioning
confidence: 76%
“…Road traffic demand decreases during adverse weather [26], which attenuates the rise in accidents, while the extent of the decrease depends on the purpose of the trip (work, shopping, holiday, etc.). The structure of road traffic, the composition of drivers (by skill level) in the traffic, and the average degree of time pressure varies between days.…”
Section: Approaches In Analysis Of Road Traffic Sensitivity To Weathementioning
confidence: 99%
“…traffic safety, reliability of travel times (Papinski et al, 2009)), and situational variables (e.g. weather conditions (Cools et al, 2010a, Cools et al, 2010c, holiday effects (Cools et al, 2009, Cools et al, 2010b and traffic information (Zhang and Levinson, 2008)). Moreover, future research should extent to other transport modes such as walking, bicycle use, public transport and carpooling.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a seasonality pattern in road accidents was expected, as a number of accidents in winter may be due to snow and slippery roads (6,17). However, we have experienced a relatively long period of drought, which has led to winters with low precipitation and blizzards, which in turn has reduced the occurrence of snow and blizzards.…”
Section: Discussionmentioning
confidence: 95%